The role of absorption capacity in innovation: evidence of practices developed by technology-based companies inserted in collaborative networks - Tonial, Graciele (2022)
There is a small number of studies that analyze the configuration of absorptive capacity in companies from emerging countries, such as Brazil. This study seeks to analyze the practices that small and medium-sized Brazilian technology-based companies apply to optimize knowledge flows and, consequently, take advantage of organizational innovations. With this objective, the research uses a qualitative approach to analyze data from a total of 11 technology-based companies. Data were collected through semi-structured interviews, non-participant observation, and document analysis. The main results indicate that absorptive capacity practices are determinants of organizational innovation, such as: adapting external knowledge to a new technology to create a new product; and the development of the capacity to apply internal and external knowledge in patents and/or innovative software products for the market. There were also differences in the practices applied by companies in the same sector, and in this line it was found that companies with more time in the market tend to have more practices implemented, which allows them to leverage their innovation processes. Our results provide concrete evidence on how to allocate knowledge resources to maximize their potential to take advantage of organizational innovations.